Authentic leadership and employees’ performance: the mediating role of affective commitment and creativity - Ribeiro, Neuza (2020)
This study aims to examine how perceptions of authentic leadership explain affective commitment, creativity and employees’ performance. A second aim is to examine the mediating role of affective commitment and creativity in the relationship between perceptions of authentic leadership and employees’ individual performance. A sample of one hundred and fourteen employees belonging to several Portuguese public and private organizations was surveyed. A quantitative methodology was used. The results indicate that authentic leadership explains affective commitment, creativity and individual performance. It is also possible to verify that affective commitment totally mediates the relationship between authentic leadership and individual performance, while creativity presents only a partial mediation of this relation. With these results, it can be verified that this style of leadership has a relevant impact on employees’ attitudes and behaviours. Additional studies with larger samples are needed to determine more clearly not only authentic leadership’s influence on individual performance but also other psychosocial variables affecting that relationship. This research has practical implications for human resources management in organizations, particularly in selection processes and training and development of leaders and managers. Practitioners looking to increase employee commitment, creativity and performance can do so by augmenting the authentic leadership.